Detecção do DNA de Mycobacterium leprae em secreção nasal - PONTES, Ana Rosa Botelho (2011)
Studies have demonstrated high sensibility of the polimerase chain reaction (PCR) technique in the identification of the Mycobacterium leprae DNA . This study aimed to evalue the PCR sensibility at the detection of the M. leprae DNA in nasal swab of leprosy patients and to compare the results with the bacilloscopy and multibacillary (MBs) and paucibacilares (PBs) forms. Nasal secretion samples of 24 leprosy patients were collected, and were preserved in one and two lise's solution. The PCR results were highly significant (p <0.0000) and they revealed grater sensibility than bacilloscopy, in several clinical forms. Nevertheless, still different studies are necessary, testing new markers and preservatives, with the purpose of lifting up the sensibility of this technique, in nasal secretion samples.